The dynamic relationship between BTC with BIST and NASDAQ indices - Ulu Cagri (Financial Internet Quarterly, 2023)
The significance of digital investment has grown substantially, enabled by advancing technology, which provides digital monitoring of investment instruments. Consequently, analyzing these instruments has become imperative. In particular, investors are inclined to compare new investment opportunities with well-established global stock markets, seeking to capitalize on their advanced financial literacy. This study aims to employ econometric analysis to explore the dynamic relationship between Bitcoin and the BIST100 and NASDAQ 100 indices. The time frame for this investigation spans from January 1, 2017, to March 10, 2022. Stationarity was confirmed through unit root tests (ADF, PP, KPSS, ZA, FADF, and FFFFF ADF) for the subsequent utilization of Autoregressive Conditional Variance Models. Additionally, Generalized Autoregressive Conditional Variance and Dynamic Conditional Correlation Tests were conducted. Results from the Dynamic Conditional Correlation Test model revealed no statistically significant dynamic conditional correlation between Bitcoin and BIST 100. Conversely, a negative and significant dynamic conditional correlation emerged between Bitcoin and NASDAQ 100. Investors should not only monitor the market but also review academic studies before making investment decisions. In this regard, this study holds significant importance. The study is limited to the BTC, BIST, and NASDAQ indices. Researchers interested in the topic can increase the dataset to further enrich the study.